Heat Transfer Analysis Of Windows With Venetian Blinds: A Comparative Study - Wright, John L.; Lomanowski, Bartosz (My University, 2007)
The potential to reduce building load and annual energy consumption is widely recognized in the use of shading devices to control solar gain. Consequently, the ability to include and model shading layers in complex glazing systems is needed in evaluating the energy performance of a building envelope. In a previous study, solar-optical calculations were presented for a window with a light and dark coloured venetian blind using simplified models for three different glazing/shading configurations. Results were presented for the hourly transmitted, reflected and absorbed quantities of solar radiation for summer and winter conditions. In this study, a heat transfer analysis is presented to complement the previous study and provide all the relevant information required for building energy analysis. The individual contributions to the net heat gain consisting of total solar transmission, longwave radiant gain and convective gain are presented. The ability to quantify the relative importance of each heat gain component offers significant insight into the thermal characteristics of complex glazing/shading systems.
Keywords: Fenestration; Venetian blind; Simulation; Comparison; Heat transfer